Prinsip Kemanfaatan Hukum dalam Pengaturan Merger yang Menciptakan Persaingan Usaha Sehat - Samawati Saleh, Putu; Wijaya, Chandra; Emirzon, Joni (Universitas Jambi, Fakultas Hukum, 2025)
Mergers are often carried out to strengthen the position of corporations in the market, in some cases mergers carried out by corporations lead to conspiracy actions that can have an impact on unfair business competition. Alleged violations of fair business competition carried out by corporations by conducting mergers have prompted KPPU to impose post-merger notification requirements, to ensure that the behaviour of mergers carried out by corporations does not disturb the principles of fair business competition. The problem is that when the merger has been carried out and it turns out that the post-merger assessment is indicated to violate fair business competition, KPPU can provide witnesses for the corporation, of course this becomes ineffective and causes losses to the parties. Based on this, a discussion on the concept of pre-notification of mergers needs to be conducted in order to fulfil the application of the principle of legal expediency in the regulation of merger notification that creates fair business competition in Indonesia. By referring to Law No. 5 Year 1999, it explains the importance of pre- and post-merger notification system. This research uses a comparative law approach that looks at how South Korea and Japan have enacted pre-notification of mergers which is in fact more effective and efficient for the implementation of competition law certainty in their countries. The findings are that the change to a pre-merger notification system will be more effective in preventing monopolistic practices, supporting fair business competition, and providing better legal certainty for business actors. This pre-merger notification acts as a repressive measure for alleged unfair business competition.